Phenolic compounds isolated from Morus nigra and their α-glucosidase inhibitory activities. Issue 5 (3rd March 2020) - Xu, Liangjin; Yu, Meihua; Niu, Lixin; Huang, Chunyue; Wang, Yifan; Wu, Chunzhen; Yang, Peiming; Hu, Xiao
Abstract: A novel benzofuranone unprecedentedly with a prenyl group at C-3, nigranol A (1 ), a new flavonol, nigranol B (2 ), and three known compounds, sanggenon M (3 ), nigrasin C (4 ), and nigrasin A (5 ) were isolated from the twigs of Morus nigra Linn. Their structures were elucidated on the basis of the analysis of multiple spectroscopic data. All of the compounds, along with eight previously isolated ones (6 –13 ) were investigated for their α-glucosidase inhibitory activities. The result showed that compounds 1 –13 except 4 exhibited prominent inhibitory activities against α-glucosidase. Among them, compounds 2 and 7 were the best α-glucosidase inhibitory candidates with IC50 values at 1.63 and 1.43 μM, respectively. Furthermore, the structure-activity relationships of the sanggenon-type flavanones were summarized. Abstract :